P01.059 Technical features of a medical device generating alternating electric fields (Tumor Treating Fields) for the treatment of glioblastoma. (19th September 2018) - Graeb, M; Kinzel, A; Kirson, E
Abstract: Introduction: Glioblastoma multiforme is a fatal and particularly difficult to treat disease. Therefore, novel therapeutic interventions to control glioblastoma are needed. Tumor Treating Fields (TTFields) are low-intensity (1–3 V/cm), intermediate frequency (100-300kHz) alternating electric fields that show anti-proliferative action in various cancer cells including glioblastoma. In the EF-14 phase 3 trial, adding TTFields to maintenance Temozolomide significantly improved median PFS and OS from randomization in newly diagnosed GBM. Currently, TTFields are approved for the treatment of adults with newly diagnosed and recurrent glioblastoma. TTFields are delivered at therapeutic intensities (intended field strength >1V/cm) by means of a portable medical device and transducer arrays (Optune® system). Materials and Methods: Here, the technical features to ensure efficacy and safety of the Optune system will be reviewed in detail. Results: The Optune system is comprised of two main components - an electric field generator (the actual device) and insulated transducer arrays. The preset electric field generator generates TTFields at a frequency of 200 KHz and up to 707mA RMS output current. The size of this battery-powered device itself is 7.1 x 2.3 x 7.6 inches with a total weight of 1.5 lbs (without the battery). The main components of the user interface are the power switch, a TTFields button, error indicator, and a low battery indicator. The device is connected to 2 pairs of transducer arrays, each made of 9 ceramic discs with high dielectric constant. During treatment, each pair of transducer arrays generates an alternating electric field that changes its polarity 200, 000 x per second (200kHz) for GBM. The electric fields switch between the transducer array pairs at every second. For patient safety, the transducer arrays are able to monitor temperature by means of 8 thermistors per array and temperatures beyond 41° C will automatically turn on an alarm and cause a treatment break. Conclusion: The Optune device is a highly sophisticated medical device intended for the treatment of glioblastoma. The device contains numerous technical features to ensure efficacy as well as patient safety. In summary, the design and technical features of the Optune device allows for treatment of glioblastoma while allowing patients to proceed with their activities of daily living.